2019
DOI: 10.1126/sciadv.aaw2399
|View full text |Cite
|
Sign up to set email alerts
|

Unusual packing of soft-shelled nanocubes

Abstract: Space-filling generally governs hard particle packing and the resulting phases and interparticle orientations. Contrastingly, hard-shaped nanoparticles with grafted soft-ligands pack differently since the energetically interacting soft-shell is amenable to nanoscale sculpturing. While the interplay between the shape and soft-shell can lead to unforeseen packing effects, little is known about the underlying physics. Here, using electron microscopy and small-angle x-ray scattering, we demonstrate that nanoscale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 56 publications
(104 citation statements)
references
References 52 publications
0
101
3
Order By: Relevance
“…From the selfassembly perspective, the challenge of creating structurally robust and ratio nally organized complex 3D nanomaterials is well recognized. For example, a comprehensive strategy for the assembly of designed NP lattices using polyhedral DNA origami constructs of different shapes (26)(27)(28)(29) and particles of different geometries (30,31) for the forma tion of diverse types of lattice symmetries has been demonstrated. Given the exquisite structural control offered by DNA in creating complex 3D structures with integrated functional nanoobjects (13,16,(32)(33)(34)(35), it is increasingly important to have the ability to translate the assembly methodology into a generation of materials that are not limited by the environmental requirements of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…From the selfassembly perspective, the challenge of creating structurally robust and ratio nally organized complex 3D nanomaterials is well recognized. For example, a comprehensive strategy for the assembly of designed NP lattices using polyhedral DNA origami constructs of different shapes (26)(27)(28)(29) and particles of different geometries (30,31) for the forma tion of diverse types of lattice symmetries has been demonstrated. Given the exquisite structural control offered by DNA in creating complex 3D structures with integrated functional nanoobjects (13,16,(32)(33)(34)(35), it is increasingly important to have the ability to translate the assembly methodology into a generation of materials that are not limited by the environmental requirements of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Our capability to measure facet-dependent interfacial stiffness and our demonstration on their role in shaping the supracrystals can advance crystal design at the nanoscale. For example, one can control the interfacial stiffness and crystal habit by utilizing the toolkits of both intrinsic parameters of NP shape and surface chemistry 41 , 54 – 56 as well as extrinsic parameters, such as temperature, pH, and ionic strength 57 – 59 . Previously reports have shown that changing the length of DNA ligands on the same gold NPs has led to tunability in the lattice symmetry of the interior structure and exposed facets of the supracrystal 17 , 55 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Through the programmable base-pairing interactions, highly ordered crystalline assemblies are extensively explored in recent years by Mirkin, Gang, and others. [9,42,[104][105][106][107][108][109][110] For the monary particle self-assembly, Mirkin and co-workers assembled triangular bipyramids (TBPs) into clathrate architectures (Figure 3a-g). [106] In their work, the uniform TBPs with ≈250 nm long edge and ≈177 nm short edge was first synthesized and then modified with 28-base hexylthiol-DNA strands.…”
Section: Nanoparticle Superlatticesmentioning
confidence: 99%